Bartonella spp. in Bats, Kenya - Kosoy, Michael; Bai, Ying; Lynch, Tarah; Kuzmin, Ivan V.; Niezgoda, Michael; Franka, Richard; Agwanda, Bernard; Breiman, Robert F.; Rupprecht, Charles E. (Emerging infectious diseases, 2010)
We report the presence and diversity of Bartonella spp. in bats of 13 insectivorous and frugivorous species collected from various locations across Kenya. Bartonella isolates were obtained from 23 Eidolon helvum, 22 Rousettus aegyptiacus, 4 Coleura afra, 7 Triaenops persicus, 1 Hipposideros commersoni, and 49 Miniopterus spp. bats. Sequence analysis of the citrate synthase gene from the obtained isolates showed a wide assortment of Bartonella strains. Phylogenetically, isolates clustered in specific host bat species. All isolates from R. aegyptiacus, C. afra, and T. persicus bats clustered in separate monophyletic groups. In contrast, E. helvum and Miniopterus spp. bats harbored strains that clustered in several groups. Further investigation is needed to determine whether these agents are responsible for human illnesses in the region.